The integration of an axial attachment to a partial joint metal prosthesis: therapeutic interests - Sara SABIR; Jihane SLAOUI; Nadia MERZOUK; Oussama BENTAHAR (International Arab Journal of Dentistry (IAJD), 2020)
Supra radicular removable prosthesis is a therapeutic choice to manage both functional and aesthetic factors, in cases of anterior, posterior, large or subtotal edentulisms. However, the success of treatment implies a preliminary and rigorous study of the prosthetic case, in addition to mastering the stages of prosthetic implementation.The purpose of this work is to describe the prosthetic steps of supra-radicular prosthesis treatment, using axial attachment, the interest of the stone models’ set up during the pre-prosthetic and the treatment phase, as well as the advantages and the limitations of this technique.